Theodore Roosevelt for the defense : the courtroom battle to save his legacy - Abrams, Dan, 1966-; Fisher, David, 1946- (Hanover Square Press, 2019)
Chronicles the epic 1915 libel case in which Theodore Roosevelt, weighing a last presidential run, turned on former allies to challenge corruption in the political party that made him.